Livres e escravos : população e mortalidade na Madre de Deus de Porto Alegre (1772-1872) - Scott, Dario, 1963- (2020)
Orientadores: Maria Silvia Casagrande Beozzo Bassanezi, Everton Emanuel Campos de Lima